Pengaruh Fasilitas Objek Wisata Terhadap Kepuasan Wisatawan di Bukit Si Bea-Bea Desa Partungko Naginjang Kabupaten Samosir - Theresia Hutahaean (Jurnal Ilmiah Akomodasi Agung, 2022)
This study aims to describe the efforts of the Department of Culture and Tourism on the influence of tourist attraction facilities on tourist satisfaction to visit tourist objects to visit the Bea-Bea hill tourist attraction, Samosir Regency. The respondents in this study amounted to 100 people including the community and beach tourists in Samosir Regency. The tool used to collect data is a questionnaire and Likert scale technique is used to analyze and describe the results. The results showed that the influence of tourist attraction facilities on tourist satisfaction to visit the Bea-Bea hill tourist attraction. Samosir Regency is the development of transportation infrastructure to improve accessibility and connectivity from the Bea-Bea hill area of ​​Samosir Regency. Because it functions as a promotion and service, transportation needs to continue to be addressed and developed considering that it is able to create place value and time utility. ) which fosters attraction and distribution in the transfer of goods and passengers by all relevant parties and agencies, especially at the Toba Regency Culture and Tourism Office. Where the interest of tourists in Si Bea-Bea Hill, Samosir Regency, is based on the references of visitors and users of Si Bea-Bea hill including transportation, adequate facilities, cleanliness and arrangement of infrastructure and other supports including housing and other environments. As for the efforts of the Department of Culture and Tourism in influencing tourist attraction facilities to tourist satisfaction to visit Si Bea-Bea tourist attraction, Samosir Regency has not been carried out. The factors that encourage domestic tourists to use Si Bea-Bea hill, Samosir Regency, are the existence of good and complete facilities.